[abstrakt ...]. - Christiaens A. X. (jaar 1935?, 2003)
deel van map CIV_151
vak: onbekend gesigneerd op achterkant
eigendom van Stad Gent Herkomst: KASK CIV_151_20
kunstwerk
Keywords: Christiaens A. X